The Islamic Education in Brunei: The Philosophy of Malay Islamic Monarchy (MIB), Integrating Malay Values, Islamic Teachings, and the Monarchical System - Syafitri, Linda Ayu; Fakhruddin, Fakhruddin; Asha, Lukman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to comprehensively analyze the characteristics of Islamic education in Brunei Darussalam, which is grounded in the philosophy of Melayu Islam Beraja (MIB), and to compare it with Islamic education in Indonesia, which is multicultural and democratic in nature. This research employed a qualitative approach based on a literature review by examining documents, regulations, books, and relevant studies. The findings indicate that MIB serves as a strong ideological framework shaping the curriculum, educational vision, and learning practices in Brunei, resulting in a homogeneous, coherent, and Islamic monarchy–oriented education system. Conversely, the Islamic education system in Indonesia has developed within a context of cultural diversity, decentralized regulations, and more complex social dynamics. The comparison reveals that Brunei excels in the consistency of its educational ideology, whereas Indonesia is more adaptive, inclusive, and responsive to global changes. This study contributes to understanding models of Islamic education development based on state philosophy and offers insights for advancing Islamic education policy in Indonesia.